Congenital adrenal hyperplasia. (August 2021) - Simpson, Helen; Hughes, Ieuan
Abstract: Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder of adrenal corticosteroid biosynthesis affecting 1/10, 000–1/15, 000 live births. The most common form is 21-hydroxylase deficiency caused by variants in the CYP21A2 gene. CAH classically presents at birth with atypical genitalia in an affected girl. Salt loss, which can be life-threatening, is the only sign in an affected newborn boy. An adolescent girl with CAH has a syndrome of hirsutism, acne and irregular periods. Treatment aims to replace adequate amounts of glucocorticoid and mineralocorticoid hormones, but avoid adverse effects such as growth suppression in childhood, and obesity and adverse metabolic profile in adult life. Serum 17OH-progesterone and adrenal androgens are increased in CAH because of 21-hydroxylase deficiency and can be useful markers to monitor treatment. Genital surgery has typically been performed around 12–18 months of age if a reduction in clitoral size is needed. However, this can damage nerves and affect later sexual function and there is concern about consent. Vaginoplasty can be deferred until puberty. Prenatal diagnosis has been refined by early non-invasive genetic testing but dexamethasone to prevent virilization of an affected female fetus is now seldom used because of concerns about long-term adverse effects.